Texting on a Smartphone While Walking Affects Gait Parameters - Sajewicz, Julia; Dziuba-Słonina, Alicja (International journal of environmental research and public health, 2023)
Cell phone use while walking is an ever-increasing traffic hazard, and leads to an augmented risk of accidents. There is a rising number of injuries to pedestrians using a cell phone. Texting on a cell phone while walking is an emerging problem among people of different ages. The aim of this experiment was to investigate whether using a cell phone while walking affects walking velocity, as well as cadence, stride width, and length in young people. Forty-two subjects (20 males, 22 females; mean age: 20.74 ± 1.34 years; mean height: 173.21 ± 8.07 cm; mean weight: 69.05 ± 14.07 kg) participated in the study. The subjects were asked to walk on an FDM−1.5 dynamometer platform four times at a constant comfortable velocity and a fast velocity of their choice. They were asked to continuously type one sentence on a cell phone while walking at the same velocity. The results showed that texting while walking led to a significant reduction in velocity compared to walking without the phone. Width, cadence, and length of right and left single steps were statistically significantly influenced by this task. In conclusion, such changes in gait parameters may result in an increased risk of pedestrian crossing accidents and tripping while walking. Phone use is an activity that should be avoided while walking.